Cleaning and caring during lockdown: social and economic impacts of covid-19 on migrant domestic workers. - Dias, N. (18th IMISCOE Annual Conference, 2021)
This paper aims to understand the impact of covid-19 on the care economy, in particular on migrant workers and how it affects the dynamics of the care market. Although the notion of ‘essential workers’ was largely debated during the global lockdown, after March, 2020, there was short coverage on how the pandemic affected particular social groups and occupations. Some workers, whose jobs remained essential, were not acknowledged for their endurance during lockdown and beyond. Gradually, some evidences have been emerging regarding the particular impact of Covid-19 on women and, in particular, women in low skilled sectors such as cleaning and caring. Given the furtherance of the recommendation to stay at home, work from home and to avoid public gatherings, a significant number of jobs are not favored with the gift of choice, having to opt between safety or income. The focus of this paper is twofold: firstly, resorting to interviews with individual migrant care workers, aims to understand the circumstances of migrant care workers before and after covid-19 to map the multiplicity of effects of the pandemic on this segment of the labor force (e.g. unemployment, income reduction, health hazards, cost of working, access to social protection, social stigma, family management, etc.); secondly, we intend to understand the effects of the pandemic on the care market itself by analyzing official statistics from the Employment Survey of the Statistics National Institute, from Unions and NGO’s dealing with migrant care workers on evaluating what types of risks and calculations are determining the presence of workers in the care economy and the eventual changes in their relation to employers.